Philippine defense policy in the 21st century: Autonomous defense or back to the alliance? - De Castro, Renato Cruz (Animo Repository, 2005)
Using the Philippines as a case study, this article addresses two theoretically relevant questions regarding alliance durability. First, why does a state, given a choice between autonomous defense (by dipping into its own domestic resources for arms build-up) and seeking allies (to provide military resources and guarantees), opt for an alliance? And two, under what conditions will a state favour alliance over autonomous defense? After nearly three decades of security efforts directed at strengthening its alliance with the United States, the Philippines in the early 1990s decided to embark on a modernization programme to provide its armed forces with an autonomous defense capability. However, a lack of financial resources and political will have prevented the Philippine government from implementing the plan. The article maintains that the Philippine government's inability to develop an independent defense posture will bind the country to its alliance with the US, the only viable current option for ensuring its security in an evolving and uncertain international system.